REVIEW: MINDSCAPING THE LANDSCAPE OF TIBET - Reviewed by Dorje, Tashi (Asian Highlands Perspectives, 2018)
Dan Smyer Yü. 2015. Mindscaping the Landscape of Tibet: Place, Memorability, Ecoaesthetics. Boston: Walter de Gruyter. 257 pp. ISBN 978-1-61451-553-1 (hardback 140USD), ISBN 978-1-61451-562-3 (paperback 42USD), ISBN 978-1-61451-423-7 (PDF 140USD), ISBN 978-1-61451-980-5 (EPUB 140USD). Dan Smyer Yü's work (2015) is an important contribution to the field of Tibetan Studies and provides thought-provoking insights on Tibetan landscapes. A professor of anthropology at Yunnan Minzu University, Yü's research interests include trans-regional studies of ethnic relations, religious diversity, and Tibetan Buddhism in the Himalayas. Yü has also been involved in the production of documentary films about Tibet and Tibetan landscape, Buddhism, and culture. In Mindscaping the Landscape of Tibet, Yü explores the potency of Tibetan landscape through the lens of post-Orientalism, with a focus on intimate interactions between place and people, and connections between landscape and mindscape. Containing extensive ethnographic descriptions and theoretical applications, Yü borrows Edward Casey's (b. 1939) concept of "placiality" as a conceptual tool, linking the "materiality and immateriality of place" (23) and exploring their manifestations. The book features eight chapters, including introduction and conclusion chapters. The remaining six chapters are case studies carried out in Sambha (Sum ba), a Tibetan community in Khri ka (Guide) County, Mtsho lho (Hainan) Tibetan Autonomous Prefecture, Mtsho sngon (Qinghai) Province; Beijing; Shangrila (Xiangelila, Sems kyi nyi zla, Rgyal thang), a Tibetan city in Bde chen (Diqing) Tibetan Autonomous Prefecture, Yunnan Province; and Lha sa. Also included are narratives of the Chinese People's Liberation Army's (PLA) arrival in Tibet in the 1950s, and analysis of the cinematic landscapes of Tibet, Tibetan intellectual critics of traditional Tibet, religious tourism, and public discourse between Tibetans and non-Tibetans. ...